Pengaruh Atmosphere Cafe, Hedonic Value Terhadap Kepuasan Konsumen di Café Pelangi Ambon ( Analisis Smart SEM PLS ) - Khaeril; Bungatang; Tokamadoran, Siti Aisa; Muhrin, Rifai (Insan Cita Bongaya Research Journal, 2023)
The Effect of Atmosphere, Hedonic Value on Consumer Satisfaction of Café Pelangi Ambon (Analysis of SMArt SEM PLS) By Khaeril Khaeril, Siti Aisa Tokomadoran dan Rifai Muhrin . This study aims to analyze the direct influence of Atmosphere, Hedonic Value on café consumer satisfaction at Café Pelangi Ambon. The research method applied is the Quantitative research method, the number of respondents in this study is 70 people. Data was analyzed using the SMART SEM PLS Version 3 Inferial Statistical Analysis Tool. The results showed that: (1) Atmosphere has a positive and significant influence on Café Consumer satisfaction at Pelangi Ambon café. (2) Hedonic Value has a positive and insignificant effect on café consumer satisfaction at café pelangi Ambon. Atmosphere has the most influence compared to Hedonic Value. It was also found that the R-Square in this model was 12.7% in the low category. This is also a good gap to conduct further research in the future, relating to variables related to café satisfaction for other city settings.